2015
DOI: 10.1186/s13053-014-0023-9
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about weight and breast cancer: an interview study with high risk women following a 12 month weight loss intervention

Abstract: BackgroundBreast cancer is the most common cancer in the UK. Lifestyle factors including excess weight contribute to risk of developing the disease. Whilst the exact links between weight and breast cancer are still emerging, it is imperative to explore how women understand these links and if these beliefs impact on successful behaviour change.MethodOverweight/obese premenopausal women (aged 35–45) with a family history of breast cancer (lifetime risk 17–40%) were invited to a semi-structured interview followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…Recent work from our group showed that women were receptive to adding a brief “cancer prevention information session” to screening or symptomatic clinics (Sinclair et al, ). However, research also highlights factors that may make communication about modifiable risk factors challenging, including beliefs about the role of luck and genetics in developing cancer (Conway, Wyke, Sugden, Mutrie, & Anderson, ; Dumalaon‐Canaria, Hutchinson, Prichard, & Wilson, ; Wright et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work from our group showed that women were receptive to adding a brief “cancer prevention information session” to screening or symptomatic clinics (Sinclair et al, ). However, research also highlights factors that may make communication about modifiable risk factors challenging, including beliefs about the role of luck and genetics in developing cancer (Conway, Wyke, Sugden, Mutrie, & Anderson, ; Dumalaon‐Canaria, Hutchinson, Prichard, & Wilson, ; Wright et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…But midlife people stay at danger zone. The young people and BMI factors have little bit risk to developing breast cancer (Kruk, 2015;Wright, 2015). Pregnancy (Britt et al, 2007) and breast feeding (Mohaghegh et al, 2015) have also association to develop breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Our participants were women at increased risk of breast cancer, although our own and other evidence suggests that their motivation for weight loss and adherence to diets tends not to differ from dieters in the general population (10,31) .…”
Section: Discussionmentioning
confidence: 93%